2016
DOI: 10.1590/2317-4889201620160066
|View full text |Cite
|
Sign up to set email alerts
|

Eustatic and tectonic change effects in the reversion of the transcontinental Amazon River drainage system

Abstract: The development of the transcontinental Amazon River System involved geological events in the Andes Chain; Vaupés, Purus and Gurupá arches; sedimentary basins of the region and sea level changes. The origin and age of this river have been discussed for decades, and many ideas have been proposed, including those pertaining to it having originated in the Holocene, Pleistocene, Pliocene, Late Miocene, or even earlier times. Under this context, the geology of the sedimentary basins of northern Brazil has been anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 58 publications
(139 reference statements)
1
25
0
5
Order By: Relevance
“…In general, however, marine incursions remain largely untested as a diversifying force (Noonan & Wray, 2006;Garda & Cannatella, 2007;Antonelli et al, 2009). In addition, it is reported that in early Miocene, the Purus arch was still active, and was a prominent landscape feature in central Amazon (Wesselingh & Salo, 2006;Figueiredo et al, 2009;Caputo & Soares, 2016) thus this geological formation also could explain the east-west pattern as well. While other hypotheses, such as Pleistocene refugia have also been proposed to explain this east-west pattern of diversity (Pellegrino et al, 2011), the Miocene marine incursions have the best temporal concordance with the basal east-west divergence pattern observed in Amazophrynella and other Amazonian anuran groups.…”
Section: Discussionmentioning
confidence: 99%
“…In general, however, marine incursions remain largely untested as a diversifying force (Noonan & Wray, 2006;Garda & Cannatella, 2007;Antonelli et al, 2009). In addition, it is reported that in early Miocene, the Purus arch was still active, and was a prominent landscape feature in central Amazon (Wesselingh & Salo, 2006;Figueiredo et al, 2009;Caputo & Soares, 2016) thus this geological formation also could explain the east-west pattern as well. While other hypotheses, such as Pleistocene refugia have also been proposed to explain this east-west pattern of diversity (Pellegrino et al, 2011), the Miocene marine incursions have the best temporal concordance with the basal east-west divergence pattern observed in Amazophrynella and other Amazonian anuran groups.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of an exposed area that continues underground to the West, under the Içá and Solimões formations [30]. The Alter do Chão Formation is represented by the fluvio-lacustrine and fluvial deposits of Cenozoic age [31], consisting of medium to coarse sandstone with clay fragments, medium to coarse caulinitic sandstone, fine sandstone, massif mudstone interbedded with thin to medium sandstone and mudstone.…”
Section: Hydrogeological and Climate Settingmentioning
confidence: 99%
“…Atlantic incursions are believed to have followed the present course of the Amazon (Nores 1999, Hubert andRenno 2006) and must have either been of exceptional size (as described in Nores 1999 but not supported in recent literature as explained below) or taken place after the Amazon's course had developed, due to geological barriers at earlier time periods (Caputo and Amaral 2016). The existence of such east-west incursions is disputed in Rossetti et al (2005).…”
Section: Marine Incursion Modelmentioning
confidence: 99%
“…Another paleogeography model, the lake model, states that tectonic activity caused a downwarping of part of the Amazon Basin, resulting in a large lake covering much of the western and central portions of Amazonia and having at various times an outlet either to the north through the Orinoco River or to the east through the current mouth of the Amazon (Frailey et al 1988). The current outlet and east-west orientation of the Amazon is believed to have arisen only at the end of the Miocene (Figueiredo et al 2009, Caputo andAmaral 2016). Such a lake would have separated the Brazilian and Guianan Shields in the east, made up of Precambrian rock, from the newly raised Andes in the west for much of the Miocene, with lakes or seas separating the two shields as well, resulting in differentiation of organisms in all three areas (Aleixo and Rossetti 2007).…”
Section: Amazonian Lake Modelmentioning
confidence: 99%